Collective capacity building : shaping education and communication in knowledge society - Sava, Simona; Borca, Claudia; Clitan, Gheorghe (International issues in adult education., 2020)
"The theme of Collective Capacity Building (CCB) is a comprehensive one, resonating with the complexity of the knowledge society. Such complexity requires contributions of a wide range of scientists, for a multidimensional understanding. Thus, philosophers, economists, educationalists, sociologists, political scientists, psychologists, scientists from Romania, Germany, Spain, Serbia, Greece, Cyprus, Latvia and Sweden have come together in Collective Capacity Building: Shaping Education and Communication in Knowledge Society. Their choice to discuss current societal challenges in different fields, in a transdisciplinary and interdisciplinary manner, illustrates how communication, education, interaction, identity, science, professionalization and others are (re)shaped nowadays. As it is increasingly evident that the challenges of a knowledge-based society are more resilient to traditional approaches and the new focus is on how to regulate new skills and capacities, the contributions propose a more stimulating reflection and dialogue on how CCB can foster progress in some of the most intricate educational, social, cultural, geopolitical and economic issues today. In light of this, the contributors have addressed the following questions: How can we define collaboration in communication and educational theory and practice? What are the tools and the rules adopted by CCB in various practical contexts? How can researchers develop their theoretical perspective on CCB after their thorough investigation of current and complex educational issues and societal challenges?"--